Fistula Prevention Awareness Activities of Community Volunteerism Niger: A way to improve Access to Information and Care - Ibrahim, Souley; Diop, Ndeyi Altine; Mounkaila, -; Traore, Habsatou; Tripathi, Vandana (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess the effects of community volunteer (CV) activities on use of maternal and reproductive health services in Niger. The USAID-funded Fistula Care Plus Project (FC+) strengthens fistula prevention, detection, treatment and reintegration. In Niger, FC+ engaged CVs to increase facility delivery, promote pre- and post-natal care and to improve access to family planning (FP) in Tahoua and Maradi health districts. Methods: FC+identified CVs and trained them to explain obstetric fistula, identify pregnancy danger signs, promote safe motherhood, and discuss male involvement. CVs provide community monitoring through household visits and awareness activities. CVs collect data on pregnant women, follow up on antenatal (ANC)/post-natal (PNC) visits, and provide counseling on all FP methods. We used routine facility data to summarize maternal health service usage in Tahoua and Maradi. Results: 774 CVs were trained between March 2015 and April 2016; they held 9,999 community outreach events, reaching 98,654 individuals. The number of women completing their first ANC visit increased from 13,041 in 2015 to 14,978 in 2016 (15%). 12% and 25% increases were documented, respectively, for fourth ANC visit and PNC visit completion in 2016 relative to 2015.A 48% increase in new acceptors of long-acting FP methods also occurred. Data require standardization against population changes and triangulation with qualitative data from community stakeholders. Conclusions: Engaging community volunteers may improve access to information and services, resulting in increased use of FP and maternal health care. A follow-up system to ensure continued engagement among stakeholders could promote sustainability.